Circadian system from conception till adulthood - Sumova, Alena; Sladek, Martin; Polidarova, Lenka; Novakova, Marta; Houdek, Pavel (Progress in brain research, 2012)
In mammals, the circadian system is composed of the central clock in the hypothalamic suprachiasmatic nuclei and of peripheral clocks that are located in other neural structures and in cells of the peripheral tissues and organs. In adults, the system is hierarchically organized so that the central clock provides the other clocks in the body with information about the time of day. This information is needed for the adaptation of their functions to cyclically changing external conditions. During ontogenesis, the system undergoes substantial development and its sensitivity to external signals changes. Perinatally, maternal cues are responsible for setting the phase of the developing clock, while later postnatally, the LD cycle is dominant. The central clock attains its functional properties during a gradual and programmed process. Peripheral clocks begin to exhibit rhythmicity independent of each other at various developmental stages. During the early developmental stages, the peripheral clocks are set or driven by maternal feeding, but later the central clock becomes fully functional and begins to entrain the periphery. During the perinatal period, the central and peripheral clocks seem to be vulnerable to disturbances in external conditions. Further studies are needed to understand the processes of how the circadian system develops and what degree of plasticity and resilience it possesses during ontogenesis. These data may lead to an assessment of the contribution of disturbances of the circadian system during early ontogenesis to the occurrence of circadian diseases in adulthood.
Keywords: cirkadiánní rytmus; Circadian Rhythm; CLOCK Proteins; proteiny CLOCK; lidé; Suprachiasmatic Nucleus; nucleus suprachiasmaticus; Humans